Dynamic Neuro-Cognitive Imagery (DNITM) Improves Developpé Performance, Kinematics, and Mental Imagery Ability in University-Level Dance Students - Abraham, Amit; Gose, Rebecca; Schindler, Ron; Nelson, Bethany H.; Hackney, Madeleine E. (Frontiers in Psychology, 2019)
ABSTRACT Dance requires optimal range-of-motion and cognitive abilities. Mental imagery is a recommended, yet under-researched, training method for enhancing both of these. This study investigated the effect of Dynamic Neuro-Cognitive Imagery (DNI™) training on developpé performance (measured by gesturing ankle height and self-reported observations) and kinematics (measured by hip and pelvic range-of-motion), as well as on dance imagery abilities. Thirty-four university-level dance students (M age = 19.70 + 1.57) were measured performing three developpé tasks (i.e., 4 repetitions, 8 consecutive seconds hold, and single repetition) at three time-points (2 x pre-, 1 x post-intervention). Data were collected using three-dimensional motion capture, mental imagery questionnaires, and subjective reports. Following the DNI™ intervention, significant increases (p < .01) were detected in gesturing ankle height, as well as in hip flexion and abduction range-of-motion, without significant changes in pelvic alignment. These gains were accompanied by self-reported decrease (p < .05) in level of difficulty experienced and significant improvements in kinesthetic (p < .05) and dance (p < .01) imagery abilities. This study provides evidence for the motor and non-motor benefits of DNI™ training in university-level dance students.